The Ethics of Territorial Borders - Williams, J. author. aut Link
X, 176 p.
Keywords: The Ethics of Territorial Borders develops a distinctive line of argument, drawing on political theory and geography as well as international relations. Unusually, this book argues for the ethical significance of borders themselves, pointing to their role in human diversity and the enduring appeal of territorial division.